A comparative study on the accuracy of noninvasive thermometers - Fadzil, F.M.; Choon, D.; Arumugam, K. (2010)
Background This study assessed the concordance of the temperatures of the digital, liquid crystal forehead and digital infrared tympanic thermometers with the mercury in glass thermometer. Methods Temperatures in degrees celsius were taken simultaneously using the four thermometers in 207 patients at the casualty department of a Malaysian hospital. The Bland Altman statistical test was used to assess the concordance by the 95% limits of agreement between the three newer thermometers and the mercury in glass thermometer. Results The digital thermometer gave the best concordance (limits of agreement 0.48-0.59 degrees C). The liquid crystal forehead thermometer gave the least concordance (limits of agreement -1.14-0.98 degrees C). The digital infrared tympanic was in between (limits of agreement -0.88-0.85 degrees C). Discussion The digital thermometer provides the best agreement with the mercury in glass thermometer. The infrared tympanic thermometer may be a preferable option for the uncooperative patient. The liquid crystal forehead thermometer is best used at home.